Teaching the Beburon Dictionary in Balinese Language and Script in Salupangkang Village - Yus Aditya, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The Balinese language plays a crucial role in preserving the cultural identity of the Balinese people, serving both as a means of communication and a symbol of unity. However, the challenge of maintaining the language's relevance among the younger generation is becoming increasingly apparent, particularly in transmigrant areas. The KKN Nusantara IV program seeks to address this challenge through the innovation of the